2020
DOI: 10.1515/text-2019-2050
|View full text |Cite
|
Sign up to set email alerts
|

Rhetorical Structure Theory and coherence break identification

Abstract: This article examines the claim of Rhetorical Structure Theory (RST) that violations of RST diagram formation principles indicate coherence breaks. In doing so, this article makes a significant contribution to the testing of RST. More broadly, it indicates that examining the coherence-break identification potential of coherence theories could help specify each theory’s purview and, in the long term, lead to the creation of hybrid models of coherence. Moreover, it paves the way for the development of training r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…The findings above have confirmed that the use of some figurative language: symbols and idioms lead to gender bias. These findings support the studies of Andersen, Emilie and Holsting (2018), Boeynaems, Burgers and Konijn (2021), Lule (2007), Moragas-fernández, Calvo and Capdevila (2018) and Skoufaki (2019) that the way of employing words determines the proposition being built. In some cases, using those two in question places women higher than men.…”
Section: Mssupporting
confidence: 89%
“…The findings above have confirmed that the use of some figurative language: symbols and idioms lead to gender bias. These findings support the studies of Andersen, Emilie and Holsting (2018), Boeynaems, Burgers and Konijn (2021), Lule (2007), Moragas-fernández, Calvo and Capdevila (2018) and Skoufaki (2019) that the way of employing words determines the proposition being built. In some cases, using those two in question places women higher than men.…”
Section: Mssupporting
confidence: 89%
“…Some difficulties relating to the top-level organization of texts are covered, and the more specific planning such as the selection of discourse markers and clause arrangement has been examined. In Sophia Skoufaki (2009) research paper entitled " An Exploratory Application of Rhetorical Structure Theory to Detect Coherence Errors in L2 English Writing: Possible Implications for Automated Writing" she presents a preliminary investigation into the viability of using Rhetorical Structure Theory (RST) (Mann & Thompson, 1988) to identify coherence errors made by Taiwanese low-intermediate English learners. For three reasons, it is believed that this inquiry is necessary.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Depending on the specific context they are addressing, speakers may use different words, skills, styles, dialects, or other linguistic aspects (Briones, 2016;Davies & Bentahila, 2008;Devianty, 201;Green & Wei, . 2014;Martin & Zappavigna 2019;Skoufaki, 2019;Scott-Baumann, 2011;Tomoyuki, 2021;Zhan & Huang. 2018).…”
Section:  Introductionmentioning
confidence: 99%